2018
DOI: 10.1097/cin.0000000000000451
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nursing Informatics in the Automation of Pneumonia Quality Measure Data Elements

Abstract: Core measures are standard metrics to reflect the processes of care provided by hospitals. Hospitals in the United States are expected to extract data from electronic health records, automated computation of core measures, and electronic submission of the quality measures data. Traditional manual calculation processes are time intensive and susceptible to error. Automated calculation has the potential to provide timely, accurate information, which could guide quality-of-care decisions, but this vision has yet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…As its significance for improving the efficiency of nursing practice has been demonstrated, informatics competency has emerged as an important competency [7,15]. Additionally, with the recent increase in the utilization of various information technologies for performing EBP, the importance of informatics competencies as a measure of the ability to perform and use EBP has also been highlighted [15,16]. Prior research has shown that information literacy education can be utilized to improve EBP knowledge [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…As its significance for improving the efficiency of nursing practice has been demonstrated, informatics competency has emerged as an important competency [7,15]. Additionally, with the recent increase in the utilization of various information technologies for performing EBP, the importance of informatics competencies as a measure of the ability to perform and use EBP has also been highlighted [15,16]. Prior research has shown that information literacy education can be utilized to improve EBP knowledge [17,18].…”
Section: Introductionmentioning
confidence: 99%